MOBILIZING PRIVATE FINANCE FOR PUBLIC GOOD: CHALLENGES AND OPPORTUNITIES OF SOCIAL IMPACT BONDS - Trotta, Annarita; Caré, Rosella; Severino, Raffaella; Migliazza, Maria Cristina; Rizzello, Alessandro (European Scientific Journal, ESJ, 2015)
Social Impact Investing (SII), defined as investment that aims to create a positive social impact in addition to a financial return, is a promising approach to solving pressing social issues. One of the key topics in this context is a new â€œpay-for-performanceâ€ financing instrument for social services that has been implemented in the UK, the US and Australia to facilitate impact investments: Social Impact Bonds (SIBs). The extension of the scope of the SIB outcomes-based model to achieve improved social outcomes in developing countries implies the use of Developing Impact Bonds (DIBs). The adaption of the SIB approach for developing countries is the most recent financial innovation derived from the impact investing industry. This work using a multiple case study approach, provides an analysis of the role of typical financial instruments of SIIin welfare policies through a descriptive and explorative analysis of the contractual scheme and of the technical and economic aspects of some currently existing SIBs and DIBs and provides a comparison of SIBs and DIBs by highlighting their similarities, differences, opportunities and challenges. The results offer practical suggestions for professionals and policy makers to support suitable strategies for the evolution of these instruments in the delivery of welfare services.